Sociologia no ensino médio : Lei nº 10.639/2003 e formação antirracista - Siqueira, Yamilia de Paula (2020)
This dissertation is the result of a research process carried out in the Post Graduation Program of Professional Master's in Education (PPGMPE) of the Federal University of Espírito Santo (UFES) and it is intended to present an analysis of the challenges faced by future Sociology teachers in the initial training period and the potential of a “Training and Research Course in Education of Ethnic-Racial Relations”, regarding the fight against racism and its confrontation. In order to meet that demand, a historical contextualization of the enactment of Law No. 10.639/2003 was conducted and also the consolidation of Sociology in the basic education level in the country's recent history; we listed theoretical data; and analyzed legal documents regarding the Education of Ethnic-Racial Relations. Our methodological choice was for action research, from which we selected and studied a group of Social Sciences Degree course finalists students at UFES, scholarship holders of the Pedagogical Residency Program during the second semester of the academic year of 2019, inserted in the training and research course; at the same time, we were able to verify the consequences of the actions performed by them in their involvement with the teaching of Sociology and in the struggle against racism. We selected some authors who were crucial to the research, namely: Gomes (2005, 2008, 2013), bell hooks (2013), Munanga (1994, 2003), Hall (2006), Freire (1985, 1996), Oliveira (2018, 2014), among others. In summary, the research resulted in an educational product, which we hope will be used as a formative tool, in order to boost other training initiatives for future Sociology teachers and professionals from other areas, as we know that the anti-racist struggle is everyone's task